Acceptance and Commitment Therapy versus Tinnitus Retraining Therapy in the treatment of tinnitus: A randomised controlled trial - Westin, Vendela Zetterqvist; Schulin, Mikael; Hesser, Hugo; Karlsson, Marianne; Noe, Reza Zare; Olofsson, Ulrike; Stalby, Magnus; Wisung, Gisela; Andersson, Gerhard (Behaviour research and therapy, 2011)
The study compared the effects of Acceptance and Commitment Therapy (ACT) with Tinnitus Retraining Therapy (TRT) on tinnitus impact in a randomised controlled trial. Sixty-four normal hearing subjects with tinnitus were randomised to one of the active treatments or a wait-list control (WLC). The ACT treatment consisted of 10 weekly 60 min sessions. The TRT treatment consisted of one 150 min session, one 30 min follow-up and continued daily use of wearable sound generators for a recommended period of at least 8 h/day for 18 months. Assessments were made at baseline, 10 weeks, 6 months and 18 months. At 10 weeks, results showed a superior effect of ACT in comparison with the WLC regarding tinnitus impact (Cohen’s d = 1.04), problems with sleep and anxiety. The results were mediated by tinnitus acceptance. A comparison between the active treatments, including all assessment points, revealed significant differences in favour of ACT regarding tinnitus impact (Cohen’s d = 0.75) and problems with sleep. At 6 months, reliable improvement on the main outcome measure was found for 54.5% in the ACT condition and 20% in the TRT condition. The results suggest that ACT can reduce tinnitus distress and impact in a group of normal hearing tinnitus patients. ► Compare effects of ACT with TRT and WLC regarding tinnitus distress. ► Large immediate effects of ACT on tinnitus distress. ► Superior effect of ACT compared to TRT (Cohen’s d = 0.75). ► Reliable change for 54.5% (ACT) versus 20% (TRT).